2021
DOI: 10.48550/arxiv.2108.05247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AGN feeding and feedback in Fornax A: kinematical analysis of the multi-phase ISM

F. M. Maccagni,
P. Serra,
M. Gaspari
et al.

Abstract: We present a multi-wavelength study of the gaseous medium surrounding the nearby active galactic nucleus (AGN) Fornax A. Using MeerKAT, ALMA and MUSE observations we reveal a complex distribution of the atomic (H i), molecular (CO), and ionised gas in its centre and along the radio jets. By studying the multi-scale kinematics of the multi-phase gas, we reveal the presence of concurrent AGN feeding and feedback phenomena. Several clouds and an extended 3 kpc filament -perpendicular to the radio jets and the inn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
2
3
0
Order By: Relevance
“…We found that the ensemble gas observations are consistent with that of Hα+[NII] ensemble detection in other BCGs and BGGs (purple points) from Hamer et al (2014) sample, as well with the prediction from the CCA simulations (purple shaded regions). As for the rotating disks, the ensemble gas detection is slightly deviated to a higher velocity shift compared to the predictions, as expected in rotating-driven systems (see also Maccagni et al 2021). The shift is mainly produced by the large velocity gradient observed in the those disks.…”
Section: Predictions From Cca Simulationssupporting
confidence: 75%
“…We found that the ensemble gas observations are consistent with that of Hα+[NII] ensemble detection in other BCGs and BGGs (purple points) from Hamer et al (2014) sample, as well with the prediction from the CCA simulations (purple shaded regions). As for the rotating disks, the ensemble gas detection is slightly deviated to a higher velocity shift compared to the predictions, as expected in rotating-driven systems (see also Maccagni et al 2021). The shift is mainly produced by the large velocity gradient observed in the those disks.…”
Section: Predictions From Cca Simulationssupporting
confidence: 75%
“…Although high-resolution 3D simulations of CCA and precipitation predicted a tight correlation between warm Hα filaments and hot "X-ray filaments" [40], the difficulty of removing interfering X-ray features (bubbles, shocks, fronts) has so far hindered the use of direct imaging probes. Our new finding of a tight correlation between Hα and X-ray filaments over multiple scales (Figure 1-2) corroborates models of CCA/precipitation via imaging, in addition to other complementary kinematical probes [27,[41][42][43][44][45][46].…”
supporting
confidence: 81%
“…ics from a CCA-feeding cycle, and are also comparable to those observed in several other galaxies (red points). A small deviation is that our sample shows slightly larger mean in the broadening axis, as we are including galaxies with rotation and AGN outbursts (e.g., NGC 4261), both shown to enhance the k-plot loci toward the upperright sector (Maccagni et al 2021). Moreover, our cool gas is often under-resolved (especially with SOFIA), meaning that we are only able to capture larger associations of clouds, rather than single elements, thus shifting the points toward the top region of the more ensemblelike regime, where clouds tend to drift in the macro-scale weather.…”
Section: Top-down Condensationmentioning
confidence: 83%
“…ALMA observations have detected CO emission and absorption in massive elliptical galaxies at the center of X-ray bright groups (David et al 2014;Temi et al 2018;Rose et al 2019;Maccagni et al 2021;North et al 2021). For the archetypal group NGC 5044 the CO observations suggest that the molecular gas is indeed distributed in several clouds apparently orbiting within ∼2 kpc from the center.…”
Section: Introductionmentioning
confidence: 99%